Forecasting Weekly COVID-19 Infection and Death Cases in Iraq Using an ARIMA Model - Jabardi, Mohammed Hussein; Kurmasha, Hasan Thabit; Al-Khalidy, Roaa Razaq (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Coronavirus (COVID-19) is a contagious disease by SARS-CoV-2 that causes the extreme respiratory disorder. The virus has caused a global crisis that has had repercussions on public health, well-being, and all aspects of public and economic life. Infrastructure, information sources, preventive measures, treatment protocols, and various other resources have been put in place worldwide to combat the growth of this deadly disease. This study used the "AutoRegressive Integrated Moving Average" (ARIMA) forecasting technique to estimate the weekly confirmed cases and deaths from the coronavirus epidemic in Iraq. The data collection period was June 1, 2020, until August 31, 2021. The findings demonstrated the model's high accuracy, with an RMSE of 24.168 for the training data and 32.794 for the testing data.